2018
DOI: 10.1161/hypertensionaha.118.11499
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Masked Uncontrolled Hypertension

Abstract: The prognostic relevance of masked uncontrolled hypertension (MUCH) is incompletely clear and its global impact on cardiovascular outcomes and mortality has not been assessed. The aim of this study was to perform a meta-analysis on the prognostic value of MUCH. We searched for articles assessing outcome in patients with MUCH compared to those with controlled hypertension and reporting adjusted hazard ratio and 95% confidence interval. We identified six studies using ambulatory blood pressure monitoring (12610 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 50 publications
3
64
0
1
Order By: Relevance
“…However, some other studies did not observe such an association after adjustment for potential confounding factors [32]. Recently, one systemic review and meta-analysis indicated that in 30 352 treated hypertensive patients with normal clinic BP, risks of cardiovascular events and all-cause mortality were higher in those with MUCH [33], which was defined by the same criteria as those used in our current study. Consistent with the recent published systemic review and meta-analysis [33], our current study also showed that in treated Chinese hypertensive patients, compared to those without masked hypertension, patient with MUCH had a higher absolute and relative risk of prevalent cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…However, some other studies did not observe such an association after adjustment for potential confounding factors [32]. Recently, one systemic review and meta-analysis indicated that in 30 352 treated hypertensive patients with normal clinic BP, risks of cardiovascular events and all-cause mortality were higher in those with MUCH [33], which was defined by the same criteria as those used in our current study. Consistent with the recent published systemic review and meta-analysis [33], our current study also showed that in treated Chinese hypertensive patients, compared to those without masked hypertension, patient with MUCH had a higher absolute and relative risk of prevalent cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 42%
“…Recently, one systemic review and meta-analysis indicated that in 30 352 treated hypertensive patients with normal clinic BP, risks of cardiovascular events and all-cause mortality were higher in those with MUCH [33], which was defined by the same criteria as those used in our current study. Consistent with the recent published systemic review and meta-analysis [33], our current study also showed that in treated Chinese hypertensive patients, compared to those without masked hypertension, patient with MUCH had a higher absolute and relative risk of prevalent cardiovascular diseases. Findings from our current study support the notion that a future randomized clinical trial should be conducted to evaluate whether improvement of out-of-clinic BP could further reduce cardiovascular risk in MUCH patients [34].…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, 24-h ABPM is considered to be the gold standard for diagnosing masked-hypertension [ 18 ]. The prevalence of masked-hypertension ranges up to 20% in population-based studies [ 19 ] and it is associated with target-organ damage and poor prognosis [ 20 ]. In the present study, more than 60% of our diabetic patients with no hypertension at baseline could be diagnosed with hypertension upon ABPM reflecting that masked-hypertension is a highly common disorder in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory BP monitoring (ABPM) and home BP monitoring (HBPM) are the two standard measurements of out‐of‐office BP. Their use can detect masked (uncontrolled) hypertension (normotension in office BP and hypertension in out‐of‐office BP) in individuals at the highest risk of cardiovascular events . There are three clinical phenotypes of masked hypertension: morning hypertension, daytime hypertension, and nocturnal hypertension …”
Section: Introductionmentioning
confidence: 99%